A national trauma data bank analysis of large animal-related injuries. Issue 9 (September 2021) - Buchanan, Frank R.; Cardenas, Tatiana C.; Leede, Emily; Riley, Christopher J.; Brown, Lawrence H.; Teixeira, Pedro G.; Aydelotte, Jayson D.; Coopwood, Thomas B.; Trust, Marc D.; Ali, Sadia; Brown, Carlos V.R.
Highlights: Patients involved in a LARI are moderately injured with more complex injuries occurring in the chest, head, and lower extremities. Fall from horse was the most common LARI mechanism. Overall mortality was low. Compared to non-riders, riders were more likely to sustain severe injuries to the chest and spine. Severe injury patterns were similar when comparing riders to MVC; trauma teams should approach LARI as they would an MVC. Abstract: Introduction: Large animal-related injuries (LARI) are relatively uncommon, but, nevertheless, a public hazard. The objective of this study was to better understand LARI injury patterns and outcomes. Materials and methods: We performed a retrospective review of the 2016 National Trauma Data Bank and used ICD-10 codes to identify patients injured by a large animal. The primary outcome was severe injury pattern, while secondary outcomes included mortality, hospital length of stay, ICU admission, and mechanical ventilation usage. Results: There were 6, 662 LARI included in our analysis. Most LARI (66%) occurred while riding the animal, and the most common type of LARI was fall from horse (63%). The median ISS was 9 and the most severe injuries (AIS ≥ 3) were to the chest (19%), head (10%), and lower extremities (10%). The overall mortality was low at 0.8%. Compared to non-riders, riders sustained more severe injuries to the chest (21% vs. 16%, p<0.001) and spine (4% vs. 2%, p<0.001). Compared to motor vehicle collisions (MVC), riders sustained fewer severe injuries to the head (10% vs. 12%, p<0.001) and lower extremity (10% vs. 12%, p=0.01). Compared to auto-pedestrian accidents, non-riders sustained fewer severe injuries to the head (11% vs. 19%, p<0.001) and lower extremity (10% vs. 20%, p<0.001). Conclusion: Patients involved in a LARI are moderately injured with more complex injuries occurring in the chest, head, and lower extremities. Fall from horse was the most common LARI mechanism. Overall mortality was low. Compared to non-riders, riders were more likely to sustain severe injuries to the chest and spine. Severe injury patterns were similar when comparing riders to MVC and, given that most LARI are riding injuries, we recommend trauma teams approach LARI as they would an MVC.